Space Geodesy Data Implementation for Earth System Geodynamics Monitoring: A Case Study of the Aegean Microplate - Smrčková Daša; Chromčák Jakub; Mužík Juraj; Ižvoltová Jana; Kostelecký Jan (Civil and Environmental Engineering)
The advances in geodesy that are continually occurring allow the science of investigating the Earth’s shape and size to be applied to the observation of its geodynamics as well. Space geodesy and remote sensing methods enable the desired phenomenon to be observed with high precision and at different scales, where the phenomenon can be global or local in nature. By tracking changes in the position of unique points on the Earth’s surface using space geodesy methods (GNSS – Global Navigation Satellite System, VLBI – Very-long Baseline Interferometry, SLR – Satellite Laser Ranging, DORIS – Doppler Orbitography and Radiopositioning Integrated by Satellite), it is possible to indirectly track the movement of the Earth system and describe changes, anomalies and their evolution over time.